Comparative studies on carbon fiber reinforced composites based on trifunctional epoxy resin and commercial epoxy resin. Issue 8 (October 2021) - Raj, Mahendrasinh; Raj, Lata; Maheta, Jaykumar; Patel, Smit
The present work focuses on comparative properties of β-naphthol based trifunctional epoxy resin and commercial epoxy resin. Reaction of β-naphthol, formaldehyde and epichlorohydrin forms trifunctional epoxy resin. β-Naphthol based trifunctional epoxy resin characterized by FT-IR, elemental analysis (C, H, N, O analyzer), epoxy equivalent weight (EEW), weight average molecular weight( M w ) ¯, viscosity, rise in viscosity, hydrolysable chlorine content and volatile content. β-Naphthol based trifunctional epoxy resin cured by five different hardeners and used as matrix material for carbon reinforced composites. Composites were characterized by their mechanical properties, chemical resistance and thermal properties. Results showed excellent chemical and thermal resistance. All results were compared against commercially available epoxy resin (Diglycidyl ether of bisphenol-A based epoxy resin having EEW of 400). Results showed that β-naphthol based trifunctional epoxy resin was superior than commercial epoxy resin.